Individual Value System And The Use Of Upward Influence Tactics - The Impact Of Belief In Just World (BJW) - SAMARASAN, YOGEETA (2004)
Globalization has brought different cultures and values together, assimilating managers to understand ways to handle superiors, subordinates, and peers. The objective of the study is focused on examining the relationship between individual values and upward influence tactics and studying the moderating effects of BJW on the said relationship.